TOURIST’S PROFILE AND PERCEPTION TOWARDS ECOTOURISM PRODUCT IN AMBENGAN VILLAGE, SINGARAJA, BALI - Komang Trisna Pratiwi Arcana; Febianti Febianti (Journal of Business on Hospitality and Tourism, 2018)
The development of the tourism industry in the south of Bali tend to be uncontrolled and opened an opportunity for other development of alternative tourism destination in other regions of Bali such as Singaraja. One of destination with natural and cultural tourism attraction is Ambengan Village. In the increase of tourist demand, the community needs to do some innovations and development of tourism product. Furthermore, it requires to prioritize the existing market segmentation and reaching the other one. It necessary due to the existing product has some weaknesses compared to tourism product attributes. The objective of this research is to discover the tourist’s profile and their perception of ecotourism product in Ambengan Village with qualitative and quantitative method. To obtain the data, the research instruments used were questionnaire to 100 mixes of domestic and international tourist, interview guidelines to government, village chief, local community, and checklist observation. Majority of the tourist were satisfied with natural attraction been offered, informative local people, and safety atmosphere surrounding area. The local community has been aware of tourism potential in their village. They are in the state of euphoria level. However it wasn't completed with other supported attributes such as accommodation; restaurant; accessibility; route direction; moneychanger and souvenir shop. Government needs to allocate more budgets in supervising the community to develop tourism potential. The data obtained also assists them practically to create marketing strategy and guidance of ecotourism product in Ambengan Village.